Constitutionalization of environmental law - Huerta Guerrero, Luis Alberto (2013)
This article analyzes how Environmental Law can take intoconsideration some of fundamental rights study categories, by a constitutional point of view, particularly the right to a balanced and appropriate environment recognized in article 2, paragraph 22 of the 1993 Peruvian Constitution in order to develop policies oriented to implementation of constitutional legal status for environment rights and property.